Pemberdayaan Sumber Daya Manusia dengan Pemanfaatan Kearifan Lokal Melalui Pelatihan Keterampilan dan Usaha Pembuatan Kue Semprong di Desa Sakatiga Sumatera Selatan - Ika Widiastuti; Muhammad Syarif Hartawan (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
The problem in Sakatiga Village, South Sumatra, is the transition of the harvest season. Community service activities are carried out in Sakatiga Village. The aim of the service is to create benefits and provide insight into the development of rice commodities that have sales value through the process of making rice commodity products so as to take advantage of the transition time. The technique for implementing this activity includes direct observation and interviews with the Sakatiga Village Head and several seasonal farming families. The methodology is carried out using lectures, discussions and experiential learning. The results of this service activity are very positive for the village community. This can be seen from 73% answering that the activity provided benefits and 27% answered adding insight to the people of Sakatiga Village